2011
DOI: 10.1038/nature10382
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics reveals deep molluscan relationships

Abstract: Evolutionary relationships among the eight major lineages of Mollusca have remained unresolved despite their diversity and importance. Previous investigations of molluscan phylogeny, based primarily on nuclear ribosomal gene sequences1–3 or morphological data4, have been unsuccessful at elucidating these relationships. Recently, phylogenomic studies using dozens to hundreds of genes have greatly improved our understanding of deep animal relationships5. However, limited genomic resources spanning molluscan dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
393
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 436 publications
(438 citation statements)
references
References 36 publications
(64 reference statements)
27
393
4
1
Order By: Relevance
“…However, we recommend adding more species per family in future studies in order to fully resolve internal relationships, especially within Golfingiidae. In the present case, increasing the amount of data from a few selected genes to hundreds of coding genes has enabled us to confirm previous molecular studies and resolve the last remaining controversies among sipunculan family relationships, supporting phylogenomics as an effective tool for resolving not only sipunculans, but also complex relationships within other spiralian clades, as shown by several recent studies (e.g., Smith et al, 2011;Kocot et al, 2011;Weigert et al, 2014).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, we recommend adding more species per family in future studies in order to fully resolve internal relationships, especially within Golfingiidae. In the present case, increasing the amount of data from a few selected genes to hundreds of coding genes has enabled us to confirm previous molecular studies and resolve the last remaining controversies among sipunculan family relationships, supporting phylogenomics as an effective tool for resolving not only sipunculans, but also complex relationships within other spiralian clades, as shown by several recent studies (e.g., Smith et al, 2011;Kocot et al, 2011;Weigert et al, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…The systematic community has necessarily progressed from candidate genes through EST-based methods to 454 and Illumina-based transcriptome and genome datasets to resolve major relationships among the animal phyla (e.g., Dunn et al, 2008;Hejnol et al, 2009;Nosenko et al, 2013;Ryan et al, 2013;Moroz et al, 2014). Long outstanding issues have been resolved for within-phylum relationships among arthropods, molluscs, and annelids, to mention just some of the largest animal phyla (e.g., Meusemann et al, 2010;Kocot et al, 2011;Smith et al, 2011;Struck et al, 2011;von Reumont et al, 2012;Andrade et al, 2014;Weigert et al, 2014). A third wave now focuses on resolving lower-level phylogenetic questions, relying almost entirely on Illumina-based technology (e.g., Johnson et al, 2013; Kocot et al, 2013;Wheat and Wahlberg, 2013;Dell'Ampio et al, 2014;Fernández et al, 2014aFernández et al, , 2014b.…”
Section: Introductionmentioning
confidence: 99%
“…Such a monophyletic Conchifera would simply require shifting the position of the root by one node, from between Aculifera þ Cephalopoda and all the other molluscs to between Aculifera and all the other molluscs. This topology was recently found by Kocot et al [52]. Recent studies investigating rooting issues in other phyla have demonstrated that subtle misrooting can be very difficult to detect, but can be discerned through experiments designed to separate historical signal from systematic error [65,66].…”
Section: Discussion (A) Aplacophorans Are Derived Chiton-like Molluscsmentioning
confidence: 85%
“…For example, large-scale sequencing projects have been undertaken for many important clades, in which hundreds of loci are sequenced (e.g. Dunn et al, 2008;Regier et al, 2010;Kocot et al, 2011;Chiari et al, 2012;Struck et al, 2011;Jarvis et al, 2014;Weigert et al, 2014). Yet, at the same time, most species in many clades may still have data for no more than a few genes each (see below).…”
Section: Introductionmentioning
confidence: 99%